Criminologists’ Perspective of Factors Contributing to Unreported Narcotics Crimes - Perkasa, Muhammad Merpi Agung (Ius Poenale, 2023)
Efforts to address and eliminate narcotics crimes heavily depend on community involvement, particularly in reporting such offenses, yet many hesitate due to various reasons. This research explores factors that hinder individuals from reporting narcotics crimes and seeks effective strategies to combat this issue, employing both normative juridical and empirical juridical approaches, including literature reviews and field studies, and analyzing data qualitatively. An example from Decision Number: 522/Pid.Sus/2022/PN Tjk, where defendant Ali Amarsyah Bin Misran was sentenced to eight months for a narcotics offense, highlights the legal consequences of such crimes. The research identifies key factors discouraging reports: the inconvenience of legal processes, fear of retaliation from criminals, and a lack of awareness about legal protections for informants. To counteract these issues, the research recommends non-penal measures such as public education on legal rights and protections, alongside penal strategies that involve thorough inquiries and investigations to collect evidence and identify suspects in unreported narcotics activities. This dual approach emphasizes a holistic strategy to boost public cooperation with law enforcement and enhance the effectiveness of narcotics crime prevention and prosecution.